A Review on Combustion Characteristics of Ammonia as a Carbon-Free Fuel - Li, Jun; Lai, Shini; Chen, Danan; Wu, Rongjun; Kobayashi, Noriyuki; Deng, Lisheng; Huang, Hongyu (Frontiers in Energy Research, 2021)
A comprehensive review of combustion characteristics of ammonia (NH 3 ) as a carbon free fuel is presented. NH 3 is an attractive alternative fuel candidate to reduce the consumption of fossil fuel and the emission of CO 2 , soot, and hydrocarbon pollutants, due to its comparable combustion properties, productivities from renewable sources, and storage and transportation by current commercial infrastructure. However, the combustion properties of NH 3 are quite different from conventional hydrocarbon fuels, which highlight the specific difficulties during the application of NH 3 . Therefore, this paper presents comparative experimental and numerical studies of the application of NH 3 as a fuel during combustion process, including the combustion properties of laminar burning velocity, flame structures, pollutant emissions for the application of NH 3 as a carbon free fuel. This paper presents the burning velocity and pollutant emissions of NH 3 alone and mixtures with other fuels to improve the combustion properties. The aim of this paper is to review and describe the suitability of NH 3 as a fuel, including the combustion and emission characteristics of NH 3 during its combustion process.